Pilates flexible strength moves for beginners & intermediate (Australia : the Derann Group, 2001)
The Pilates Method provides an excellent way to firm and tone your body, generating a natural slenderness and overall sense of well-being
Title from container
DVD format
Keywords: Pilates method; Exercise; Physical fitness